Strategi Competitive Advantage Untuk Meningkatkan Kinerja Perusahaan Jasa Konstruksi : Studi Pada PT Multi Fabrindo Gemilang - Mugiyatna; Sihite, Mombang; Derriawan (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2023)
This study aimed to determine the effect of Customer Relation Management, Innovation, HR Competence and Competitive advantage on the company’s performance directly or indirectly on the construction services of PT Multi Fabrindo Gemilang. The research sample was 151 employee respondents for focus group discussions (FGD) attended by the company’s top management. The sampling technique used is purposive sampling. They collected data using questionnaires and focus group discussions (FGD). The data analysis technique used Structural Equation Modeling (SEM) analysis which was processed with Smart PLS version 3 software, and qualitative data analysis used IFE, EFE, CPM, SWOT and QSPM analysis. The results showed that the Customer Relationship Management variable affected competitive advantage, the innovation variable had an effect on competitive advantage, the HR Competence variable had an impact on the Competitive Advantage, the Customer Relationship Management variable had no effect on the company’s performance, the innovation variable had an impact on the company’s performance, the HR competence variable affected the company’s performance. Company performance and competitive advantage variables affect the company’s performance. The results of QSPM produce alternative strategies: Strengthening and Expanding Networking, Innovation & Technology Development, and Cost Efficiency.